Influence of text luminance, text colour and background luminance of variable-message signs on legibility in urban areas at night. (May 2021) - He, Y; Li, Y; Xing, L; Qiu, Z; Zhang, X
Variable-message signs, which are an important type of traffic sign, have been widely used in traffic control. This study examines the influence of text luminance, text colour and background luminance of variable-message signs on legibility in urban areas under night-time vision. First, the background luminance of variable-message signs in typical urban areas is investigated, tested and classified as high, medium or low depending on the obtained values (3.0, 1.0 or 0.1 cd/m 2, respectively). Second, a calculation model is established for the experimental visual recognition distance under different visual acuity conditions, the experimental luminance interval is determined based on psychophysical magnitude perceived, and a legibility experiment is performed using Landolt-C rings. Finally, the reasonable luminance interval (minimum [replacement] luminance), optimal luminance and changing trends of luminance for red, green and yellow colours under different background luminances are obtained such that the legibility requirement is satisfied. The results indicated that different colours have different luminance interval and optimal luminance under different background luminances. This study is of great importance in determining the reasonable luminance of variable-message sign texts and improving the safety and efficiency of road traffic. In the future, these research results are expected to serve as guidelines for variable-message sign setup and management.